KARAKTER CINTA TANAH AIR MELALUI LITERASI KEBANGSAAN SEBAGAI SALAH SATU KULTUR SEKOLAH DI SDK RAKALABA - Bernadetha Soubyrous Yadha; Oktaviani Gua; Sarita Natalia Wona; Yosephina Emirensiana Wea Gego; Yosefina Uge Lawe (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The cultivation of a love for the homeland is an essential aspect of character education that should be instilled from an early age, particularly among elementary school students. SDK Rakalaba, as one of the elementary schools in Ngada Regency, East Nusa Tenggara, has demonstrated tangible efforts in instilling the values of patriotism through national literacy activities that are part of the school culture. This study aims to describe the implementation of national literacy as a means of fostering a love for the homeland and to identify the forms of activities and their impacts on students. The method used is qualitative descriptive, with data collection techniques including interviews, observations, and documentation. The research findings indicate that SDK Rakalaba consistently conducts various activities that reflect national literacy, such as habituating students to read books with themes of nationalism, singing the national anthem every morning, using the Indonesian language in teaching and learning activities, and organizing arts and cultural events rich in national values. Teachers and the school principal actively serve as facilitators and role models in creating a learning environment infused with a sense of nationalism. These activities have proven effective in fostering a sense of nationalism among students, such as pride in being Indonesian citizens, appreciating diversity, and demonstrating responsibility towards the school environment. Thus, the consistent cultivation of national literacy can be an effective strategy for developing a love for the homeland in elementary school settings